Solar power for the world : what you wanted to know about photovoltaics - Palz, W. (Wolfgang), 1937- (Singapore : Pan Stanford Pub., 2014)
"Published in full color, this book describes the industrial revolution associated with the implementation of electric power generation by photovoltaics (PV), the conversion of the Sun's radiation. It also describes the dramatic events in the industry that happened between 2009 and 2013: hundreds of PV companies in difficulty and the trade war between the EU and China mobilising state leaders on both sides to avoid a serious conflict. The contributing authors are protagonists all over the world who brought PV from its industrial birth in 1954 all the way up to the stormy developments during the first decade of the new century"--Provided by publisher.
pt. 1. A life for PV: Wolfgang Palz's notable role in development from the early days until now -- pt. 2. The beginning of PV in the United States -- pt. 3. PV starting a solar age in Europe -- pt. 4. PV in Asia: a dragon is waking up -- pt. 5. PV for a better developing world -- pt. 6. PV for the world.
engineering bookfair2015
Includes bibliographical references and index.
Keywords: Solar energy; Photovoltaic power generation